Metaphors dead and alive, sleeping and waking : a dynamic view - Müller, Cornelia, 1960- (University of Chicago Press, 2008)
Traditional thinking on metaphors has divided them into two camps: dead and alive. Conventional expressions from everyday language are classified as dead, while much rarer novel or poetic metaphors are alive. In the 1980s, new theories on the cognitive processes involved with the use of metaphor challenged these assumptions, but with little empirical support. Drawing on the latest research in linguistics, semiotics, philosophy, and psychology, Cornelia Müller here unveils a new approach that refutes the rigid dead/alive dichotomy, offering in its place a more dynamic model: sleeping and waking.